Telemedicine and other care models in pediatric rheumatology: an exploratory study of parents' perceptions of barriers to care and care preferences - Danielle R. Bullock; Richard K. Vehe; Lei Zhang; Colleen K. Correll (BMC, 2017)
Abstract Background The United States pediatric rheumatology workforce is committed to a mission of providing children access to pediatric rheumatology care. With a limited number and distribution of pediatric rheumatologists, telemedicine has been proposed as one way to meet this mission, yet the adoption of this modality has been slower than expected. The purpose of this study was to explore the parent perspective on barriers to accessing pediatric rheumatology care and to explore the acceptability of telemedicine and other alternative care models. Methods Over a period of six weeks, all new and return English-speaking parents/guardians of patients visiting a single center were offered an opportunity to complete a survey which assessed barriers to care and interest in alternative models of care. Responses were analyzed using descriptive statistics. Results Survey response rate was 72% (159/221). Twenty-eight percent (45/159) traveled more than three hours to the pediatric rheumatology clinic, and 43% (65/152) reported travel as inconvenient. An overwhelming majority of respondents (95%, 144/152) reported a preference for in-person visits over the option of telemedicine. This preference was similar regardless of whether respondents reported travel to the clinic as inconvenient vs convenient (inconvenient 92%, 60/65; convenient 97%, 84/87; p = 0.2881) and despite those reporting travel as inconvenient also reporting greater difficulty with several barriers to care. Those familiar with telemedicine were more likely to report a preference for telemedicine over in-person visits (27%, 3/11 vs 3%, 4/140; p = 0.0087). The option of an outreach clinic was acceptable to a majority (63%, 97/154); however, adult rheumatology and shared-care options were less acceptable (22%, 35/156 and 34%, 53/156 respectively). Conclusion Among survey respondents, in-person visits were preferred over the option of telemedicine, even when travel was noted to be inconvenient. Telemedicine familiarity increased its acceptability. Outreach clinics were acceptable to a majority. Ultimately, the parent perspective can shape acceptable ways to address barriers and provide accessible care.